Knowledge test with using test technologies as an element of improving the quality of training in e-learning systems - NEVMERZHITSKA, Elena (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The article considers the possibility of a significant improvement in the quality of education on the basis of the connection of e-Learning technology and the widespread use of tests and tasks in the test form.